(untitled) (Global Journal of Human-Social Science, 2010)
The 1990s in Lithuania can be regarded as a period of bloom of gender equal opportunities during which not only researchers who studied issues of gender equal opportunities in foreign theory and practice but also governmental structures of the highest level played a crucial role The Government of Lithuania played an active role in creating the state conception of gender equal opportunities and its realization policy Creating conditions for realizing gender equal opportunities at state level was a basis for a democratic society of the 21 st century in Lithuania These processes can be regarded as ground-breaking phenomena in post-soviet history This break in gender ideology raises a task to analyse the processes from a practical perspective to better understand its importance to socio-economic policy and social interrelations Hence the goal of this article is to analyse gender equal opportunity in post- soviet Lithuanian society from a practical perspective